Copper(I) Phosphinooxazoline Complexes: Impact of the Ligand Substitution and Steric Demand on the Electrochemical and Photophysical Properties. Issue 12 (25th February 2020) - Giereth, Robin; Mengele, Alexander K.; Frey, Wolfgang; Kloß, Marvin; Steffen, Andreas; Karnahl, Michael; Tschierlei, Stefanie
Abstract: A series of seven homoleptic Cu I complexes based on hetero‐bidentate P^N ligands was synthesized and comprehensively characterized. In order to study structure–property relationships, the type, size, number and configuration of substituents at the phosphinooxazoline (phox) ligands were systematically varied. To this end, a combination of X‐ray diffraction, NMR spectroscopy, steady‐state absorption and emission spectroscopy, time‐resolved emission spectroscopy, quenching experiments and cyclic voltammetry was used to assess the photophysical and electrochemical properties. Furthermore, time‐dependent density functional theory calculations were applied to also analyze the excited state structures and characteristics. Surprisingly, a strong dependency on the chirality of the respective P^N ligand was found, whereas the specific kind and size of the different substituents has only a minor impact on the properties in solution. Most importantly, all complexes except C3 are photostable in solution and show fully reversible redox processes. Sacrificial reductants were applied to demonstrate a successful electron transfer upon light irradiation. These properties render this class of photosensitizers as potential candidates for solar energy conversion issues. Abstract : Homoleptic Cu I complexes were synthesized and characterized based on hetero‐bidentate P^N ligands. In order to study structure–property relationships, the type, size, number and configuration of substituents at the phosphinooxazoline (phox) ligands were systematically varied.